AN EFFECTIVE METHOD FOR PRODUCTION OF VIRUS-LIKE PARTICLES, CARRYING HUMAN IMMUNOGLOBULIN EPITOPES - Kamzina, A.S.; Baltabekova, A.Zh.; Shustov, A.V. (Eurasian Journal of Applied Biotechnology, 2013)
Antigens in the form of virus-like particles (VLP) are capable of eliciting a strong humoral and cellular immune response. VLP gained popularity as a platform for the presentation of antigenic determinants of the immune system, borrowed from a huge variety of natural proteins that act as targets of the humoral response. In this study, VLP, formed by the core protein of hepatitis B virus (HBcAg), used as a carrier of human immunoglobulin E (IgE) epitope. IgE molecules are involved in the pathological mechanism of allergies and asthma. The value of the antigens described in this work is that immunization of VLP, carrying an array of IgE epitopes, is potentially capable of eliciting antibodies that block the biological effect of IgE. Thus, VLP with IgE epitopes are promising for use in therapeutic vaccine developed for the treatment of allergic diseases and bronchial asthma. The peptide of the constant portion of the human IgE (GETYQSRVTHPHLPRALMRSTTK) has been cloned into the main HBcAg immunodominant region using three types of linkers, which should provide the correct spatial arrangement of IgE epitope. An efficient method of expression and purification of VLP forming recombinant protein is described.